Crawling Data Customer Pada Aplikasi Smarsofi Untuk Layanan Digital Marketing - Maulana, Ahmad; Udayanti, Erika Devi; Sanjaya, Yusuf Yudha; Anggadiva, Rifky; Comara, Maulana Muhammadin; Muna, Mohamad Sirojul (Jurusan Teknologi Informasi Universitas Semarang, 2019)
Current communication can be carried out without having to come face to face, without limitation of space and time, namely through the internet. the availability of internet connectivity is a necessity for all people in almost all activities. The growth of internet users influences changes in the pattern of society in communicating and socializing also has an impact on business trends, one of which is the aspect of promotion and marketing. Conventional promotion through printed media has shifted to online media. Printed media turned to digital form which was then disseminated very easily through the internet to many people in general. This paper will examine the smarsofi application or smart social wifi application that utilizes connectivity accounts from wifi users to collect data. in this case is the visitor's data from a caf ©. The main objective is to facilitate the process of collecting visitors to the caf © connected to wifi, which will then be forwarded to the distribution (broadcast) of digital promotional content.